Correspondentia: A Neologism by Aquinas Attains its Zenith in Swedenborg - James F. Lawrence (Correspondences, 2017)
This article performs a word history on correspondentia, a neo-Latin construction by Thomas Aquinas in Scholastic thought attempting to interpret Aristotle on the perception of truth, and then tracks succeeding circles of the neologism’s utility. The new term “correspondentia” performs a crucial role in shaping correspondence theory in early modern hermetic thought and again in modern neo-Cartesian thought. A thread of shared discourse demonstrates an interconnected journey for the neologism from Aquinas through these contiguous conversations all the way to Swedenborg’s sophisticated esoteric “science of correspondences.” Typical of figures in Western esoteric and New Religious Movements, Swedenborg makes claims of ahistorical and direct apprehension of theosophical information regarding unseen realms, providing a useful case study for contextual analysis of how cultural transmission and interdiscursivity shape transcendental traditions. Swedenborg claims an ahistorical reception of his “science of correspondences” in his eight-volume masterwork Arcana Coelestia (1749–1756), where he lays out his first and most exhaustively demonstrated declarations of correspondences as the key to sacred scripture and to a vast bank of information on unseen realms. Analysis of primary sources and his environment of thought, however, betrays the Swedish polymath as deeply embedded in kabbalist, hermetic, and neo-Cartesian discourse for his impressive development of correspondence theory.